Cervicovaginal cellular angiofibroma. Issue 7 (16th July 2020) - Van Mulders, Sarah; Faes, Ellen; Broeckx, Glenn; Jacquemyn, Yves
Abstract : Cellular angiofibroma is a rare type of benign mesenchymal tumour that arises mostly in middle-aged women. It needs to be distinguished from other neoplasms and has a predilection for the vulvovaginal region. To our knowledge, this is the first case of a cervical cellular angiofibroma. A 34-year-old nulligravid woman was referred with a large mass bulging in the fornix posterior. Ultrasound scanning and MRI showed a large solid mass projecting in the pouch of Douglas. Laparoscopic surgical excision was performed. Histopathological examination showed a well-demarcated, unencapsulated tumour, consisting of short fascicles of spindle cells in-between thick-walled medium-sized vessels. On immunohistochemistry, there was strong reactivity with antibodies against CD34 and oestrogen receptor. Angiofibromas are benign mesenchymal tumours mostly occurring in middle-aged women. They can cause abnormal swelling and uterine bleeding and need to be distinguished from other (malignant) neoplasms.